LA CIUDAD DE LAS FANTASMAGORÍAS. LA MODERNIDAD URBANA VISTA A TRAVÉS DE SUS SUEÑOS. - Hernández Castellanos, Donovan Adrián (Andamios)
This article discusses the Marxist philosophy regarding 19th and 20th century modern cities referred to as phantasmagoria. The author comments on the urban growth and urbanization at the time and describes the influence of capitalism on these phenomena. He also considers the development of capitalism, the mercantile system, and modern governmentality (biopolitics) during this period. The philosophies of such figures as Karl Marx, Georg Hegel, and Giorgio Agamben, relating to modern cities, are also provided.